2007
DOI: 10.1207/s15327752jpa8801_11
|View full text |Cite
|
Sign up to set email alerts
|

Borderline Pathology and the Personality Assessment Inventory (PAI): An Evaluation of Criterion and Concurrent Validity

Abstract: In this study, we examined how patients diagnosed with borderline pathology (BP) would respond on the Personality Assessment Inventory (PAI; Morey, 1991) Borderline (BOR) scales in relation to patients without BP pathology. In addition, we examined whether the PAI BOR scales would be related to variables on the Social Cognition and Object Relations Scale (SCORS; Hilsenroth, Stein, & Pinsker, 2004; Westen, 1995) derived from early memory narratives. Results indicate that outpatients with a Diagnostic and Statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 28 publications
2
13
0
1
Order By: Relevance
“…Several prior studies have shown the PAI-BOR to be a reliable and valid measure of BPD features, and support the usefulness of the PAI-BOR in assessing BPD features in the general population as well as BPD in the clinical setting (Kurtz et al 1993; Trull, 1995). BellPringle et al (1997) and Stein et al (2007), for example, showed that the PAI-BOR differentiates between patients diagnosed with BPD and patients without borderline personality pathology or unscreened controls with 75% to 80% accuracy. In addition, Jacobo et al (2007) administered the PAI-BOR to patients diagnosed with BPD and found a significant correlation of 0.58 between the total number of BPD SCID-II criteria and the PAI-BOR scale.…”
Section: Discussionmentioning
confidence: 99%
“…Several prior studies have shown the PAI-BOR to be a reliable and valid measure of BPD features, and support the usefulness of the PAI-BOR in assessing BPD features in the general population as well as BPD in the clinical setting (Kurtz et al 1993; Trull, 1995). BellPringle et al (1997) and Stein et al (2007), for example, showed that the PAI-BOR differentiates between patients diagnosed with BPD and patients without borderline personality pathology or unscreened controls with 75% to 80% accuracy. In addition, Jacobo et al (2007) administered the PAI-BOR to patients diagnosed with BPD and found a significant correlation of 0.58 between the total number of BPD SCID-II criteria and the PAI-BOR scale.…”
Section: Discussionmentioning
confidence: 99%
“…Men were asked to indicate their responses to statements on a 4-point Likert-type scale ( false , slightly true , mainly true , and very true ). In prior studies, these scales have demonstrated high consistency (Gardner & Qualter, 2009) and good convergent validity with other indicators of personality disorder, including the Minnesota multi-phasic personality inventory (MMPI) and psychopathy checklist-revised (PCL-R) (Edens, Buffington-Vollum, Colwell, Johnson, & Johnson, 2002; Edens, Hart, Johnson, Johnson, & Olver, 2000; Kurtz, Morey, & Tomarken, 1993; Stein, Pinsker-Aspen, & Hilsenroth, 2007). In the current study, coefficient alpha was .80 for the Antisocial scale and .87 for the Borderline scale.…”
Section: Methodsmentioning
confidence: 99%
“…T-scores higher than 50 represent increasingly pathological emotional hyperreactivity. The PAI-BOR-A has demonstrated acceptable reliability and validity in a variety of samples (Morey, 2007, Morey, 1991, Stein et al, 2007 including BFRBD samples (Wetterneck et al, 2016).…”
Section: Maladaptive Emotional Reactivitymentioning
confidence: 97%